Analisis Model Perilaku Pengemudi Mobil Truk dalam Pemilihan Rute Jalan (Route Choice) (Studi Kasus: Jalan Tol Trans Sumatera) - Saputra, Alwafi (Jurnal Komposit: Jurnal Ilmu-ilmu Teknik Sipil, 2022)
Abstrak: Pengemudi mobil truk memilih jalan tol dengan mempertimbangkan faktor-faktor, yaitu faktor jarak dari asal ke gerbang tol, waktu perjalanan, biaya perjalanan, kemacetan, tempat peristirahatan yang tersedia dan variabel yang sangat sensitif ialah variabel kemacetan. Berdasarkan hasil data yang telah diuji dengan SPSS maka didapatkan model persamaan : Ujt = -0,441*(Jarak Gerbang Tol)-2,449*(Waktu Perjalanan)-0,820*( Biaya Perjalanan)-1,975*(Kemacet an)-0,957*(Pemberhentian). Model persamaan analisis biaya & waktu yaitu : Ujt = 0,414-0,28*(Biaya)-0,057*(Waktu). ABSTRACT Every Traveler tries to find the best route to minimize travel costs like reducing travel time by considering a few factors. These reasons are the basis for consideration of route selection. That's why necessary to conduct research on Trans Sumatera Toll Roads and Non-Toll Public Roads to determine the factors that influence the decision of truck drivers to determine the most efficient road route in terms of time and from and economic perspective. The data analysis used in this study is Binary Logistic Statistical and analysis method using IBM SPSS Statistics Software. The result of the study show, Truck drivers choose Toll Roads by considering Distance of Toll Gate, Travel Time, Travel Costs, Congestion and Rest areas. The values of these factors: Distance Of toll Gate -0.441, Travel Time -2.449, Travel Costs -0.820, Congestions -1.975, Resting Place -0.957. The most influencing factor is congestion, the model obtained is Ujt = -0.441 * (Toll Gate Distance) - 2.449 * (Travel Time) - 0.820 * (Travel Expenses) - 1.975 * (Congestion) - 0.957 * (Rest areas). The results of sensitivity test between cost and time is, truck drivers more sensitive against the time variable, the model obtained is Ujt = 0,414 – 0,28 * (Cost) – 0,057 * (Time) Keywords: driver behaviour, travel routes, Toll roads, Non-Toll public roads, route choice, Binary Logistic Method.